A systematic review of clinical outcomes and radiotherapy-associated toxicity in multicatheter accelerated partial breast irradiation. Issue 6 (February 2019) - Lv, Yang; He, Lin; Wang, Chao; Zhang, Lijiu; Zhang, Biyuan; Song, Yuhua
Abstract: Background: To integrate relevant clinical data of multicatheter accelerated partial breast irradiation (mAPBI) for reaching a comprehensive conclusion. Methods: We did 3 meta-analyses for clinical outcomes including 1740 women from 4 articles, for acute radiotherapy (RT)-associated toxicity including 1255 patients from 5 articles, and for late RT-related toxicity involving 1565 patients from 9 papers. Clinical outcomes analyses were stratified by molecular subtypes, lymph nodes status, receptor status, and human epidermal growth factor receptor 2 (HER2) status. Results: For the Luminal A/B phenotypes, the disease relapse and failure in survival significantly decreased when compared with triple negative (TN)/HER2-amplified subtypes ( P < .00001). The 5-year regional nodal recurrence (RNR), 5-year distant metastasis-free survival (DMFS) and 5-year disease free-survival (DFS) of TN patients were significantly superior to HER2-overexpression patients ( P < .00001). The 5-year cause-specific survival (CSS), 5-year DMFS and 5-year overall survival (OS) in women with lymph nodes-negative were significantly improved versus patients with lymph nodes-positive ( P = .0001). Conversely, the positive status of HER2 compared with negative one significantly increased the rate of local recurrence (LR) ( P = .02). For acute toxicity, the morbidity of dermatitis was significantly higher than hematoma and implant infection ( P = .01, P < .0001, respectively). For late toxicity, the occurrences of fibrosis (32%) and telangiectasia (14%) were significantly higher than other complications ( P < .0001). Conclusion: HER2-enriched subtype compared with other subtypes has significantly increased disease relapse and failure in survival. HER2-positive status is positively associated with an increased incidence of LR. Dermatitis is the most common acute RT-related toxicity and fibrosis is the first rife late RT-related toxicity. Abstract : Supplemental Digital Content is available in the text